Exam’s Report Automation (ERA) / Cheong Tau Han … [et al.] - Tau Han, Cheong; Aperapar, Parmjit Singh; Sian Hoon, Teoh; Wan Mohammad, Wan Nur Syazwani; Mohd Nasir, Nurul Akmal (Research Innovation Business Unit, 2014)
This project is to generate report for all the subjects with final examination automatically. Examiners need to collect data including assessment mark, ongoing assessment marks and final examination mark to enter in the program, and then a full report with graph will be generated automatically. Unlike RES which only can compute result for one group of students, ERA has the capability to compute overall result for many groups of students. Therefore, we can see the overall performance for all students taking the same subjects. This program is written using ExcEL VBA and is well designed and is user friendly.